Factors associated with low-uptake of ivermectin in Mahenge, an area with high prevalence of onchocerciasis and epilepsy in Tanzania: A qualitative perspective - Bhwana, Dan; Massawe, Isolide S.; Mushi, Adiel K.; Magili, Pendo; Amaral, Luís-Jorge; Makunde, Williams; Mmbando, Bruno P.; Colebunders, Robert (Frontiers in Tropical Diseases, 2023)
Introduction Despite over 20 years of community-directed treatment with ivermectin (CDTI) in Mahenge area in Tanzania, the prevalence of onchocerciasis has remained high (over 40% in children 6-10 years using antibody testing and 49% using skinsnips in adults). The area has one of the highest prevalence of epilepsy, exceeding 3.5% in some of rural villages. Methods Between June and July 2019, in four rural villages using qualitative methods, we assessed factors potentially associated with the persistence of high Onchocerca volvulus transmission. Results Eleven focus group discussions were organized with persons with epilepsy and their caretakers, community resource persons, and community drug distributors (CDDs), and two in-depth interviews with district programme coordinators of neglected tropical diseases (NTD). Factors considered being responsible for the persistence of onchocerciasis transmission included not taking ivermectin during CDTI for fear of adverse reactions such as itching, swelling and misconception that the drug causes infertility. Challenges for high CDTI coverage included, long walking distance by CDDs to deliver drugs to households, persons being away for farming, low awareness of the disease including the association between onchocerciasis and epilepsy and limited supervision by the NTD coordinators. Conclusion Ivermectin uptake in Mahenge should be optimised by continuous advocacy about the importance of taking ivermectin to prevent onchocerciasisassociated morbidity and by improving supervision during CDTI.